2019
DOI: 10.3390/ijms20225686
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Dicer in Adult Mice Impairs Skeletal Muscle Regeneration

Abstract: Skeletal muscle has a remarkable regenerative capacity, which is orchestrated by multiple processes, including the proliferation, fusion, and differentiation of the resident stem cells in muscle. MicroRNAs (miRNAs) are small noncoding RNAs that mediate the translational repression or degradation of mRNA to regulate diverse biological functions. Previous studies have suggested that several miRNAs play important roles in myoblast proliferation and differentiation in vitro. However, their potential roles in skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…12 Our laboratory and others recently found that muscle-specific miRNAs (myomiRs) persist for prolonged periods in the absence of the miRNA processing enzyme Dicer. 13,14 If prolonged miRNA stability is a quality specific to skeletal muscle, 15 myomiRs could be good candidates as long-term epigenetic regulators of exercise adaptation, especially given their known function in regulating muscle mass. [16][17][18] In the current investigation, we provide evidence on myonuclear accretion and maintenance in skeletal muscles with different fibre type composition and function after 2 months of PoWeR training and prolonged 6-month detraining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Our laboratory and others recently found that muscle-specific miRNAs (myomiRs) persist for prolonged periods in the absence of the miRNA processing enzyme Dicer. 13,14 If prolonged miRNA stability is a quality specific to skeletal muscle, 15 myomiRs could be good candidates as long-term epigenetic regulators of exercise adaptation, especially given their known function in regulating muscle mass. [16][17][18] In the current investigation, we provide evidence on myonuclear accretion and maintenance in skeletal muscles with different fibre type composition and function after 2 months of PoWeR training and prolonged 6-month detraining.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond myonuclear number, recent evidence suggests that DNA methylation changes in skeletal muscle induced by training could be long‐lasting and represent a memory of prior training exposure that facilitates future adaptation 12 . Our laboratory and others recently found that muscle‐specific miRNAs (myomiRs) persist for prolonged periods in the absence of the miRNA processing enzyme Dicer 13,14 . If prolonged miRNA stability is a quality specific to skeletal muscle, 15 myomiRs could be good candidates as long‐term epigenetic regulators of exercise adaptation, especially given their known function in regulating muscle mass 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies where Dicer1 was conditionally ablated in the skeletal muscle of adult mice, muscle regeneration was impaired after acute injury, but no effect on muscle morphology or function was observed during homeostasis 24,81,82 . An explanation for this difference is that in the Dicer1 conditional knockout experiments miRNA levels were only partially reduced even weeks after Dicer1 ablation, likely reflecting the high stability of these short non-coding RNAs.…”
Section: Skeletal Musclementioning
confidence: 82%
“…The role of miRNAs in muscle disorders was supported by observation that global depletion of miRNAs through Dicer knockout in mice lead to impaired muscle development [ 58 ]. CMD patient muscle has lower expression of myomiRs such as miR-1 [ 59 ], possibly due to differences in miRNA processing [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%